Maybe maybe Marisol Rainey - Kelly, Erin Entrada (Greenwillow Books, 2021)
Marisol Rainey has a big imagination and an even bigger magnolia tree in her backyard that she's way too scared to climb. But with the encouragement of her friends and family, Marisol may find the courage to climb the tree and face some of her other fears.